The crime of domestic violence and the crime of child abuse. Link, probation standard - Hegheș, Nicoleta-Elena; Franguloiu, Simona (International Journal of Legal and Social Order, 2023)
The significant increase in the number of crimes of domestic violence, maltreatment of a child, particularly and unfortunately in general and especially during the SARSCOV-2 pandemic, affecting one in three women in the European Union (Explanatory Memorandum to the Proposal for a Directive of the European Parliament and of the Council on combating violence against women and domestic violence, COM(2022) 105 final[1], requires these types of crimes to be tackled from different perspectives. The same is true of child abuse offences, which in practice often raises the question of the standard of probation and the judge's margin of discretion. From this perspective, this study aims to analyse the link between these offences, as well as the fulfilment of the condition of proving the offence “beyond any resonable doubt”, within the meaning of criminal procedural law and the requirements of the European Convention on Human Rights and Fundamental Freedoms, without dealing with this standard of proof in particular, the concept being the subject of future studies. [1] https://eur-lex.europa.eu/legal-content/RO/TXT/HTML/?uri=CELEX:52022PC0105